(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article explores the significance of regional performance styles within the broader framework of musical culture, emphasizing their essential role in the preservation and expression of cultural heritage. Regional performance styles represent one of the foundational elements of both national and local musical traditions, serving as vehicles for transmitting the cultural and aesthetic values of diverse peoples through specific performance techniques, intonational patterns, and symbolic imagery. The paper examines the unique characteristics of local performance styles, their contribution to musical education and artistic practice, and the challenges they face in the context of modern globalized culture. Furthermore, it highlights the necessity of preserving these styles as valuable expressions of intangible cultural heritage and discusses contemporary approaches and strategies for ensuring their sustainability and continued relevance in the modern era.